Drawing workshop for kids : process art experiences for building creativity and confidence - Caughey, Samara (Quarry Books, 2021)
"Drawing Workshop for Kids is for art educators, parents, teachers, and caregivers looking for an alternative to the rigid, conservative idea of "realistic" drawing projects for kids, with 25+ projects that build confidence and create independent and flexible thinking. Help kids build confidence and find their own creative voice through this collection of 25+ invitations for drawing. In Drawing Workshop for Kids, art educator Samara Caughey, founder of the highly praised family-centred art studio Purple Twig, shares drawing activities that support the development of creative, confident children ages 5 and up. All kids need to begin engaging in the pleasure of these simple yet inspiring drawing projects are a pencil and paper. Along the way, new materials are introduced, giving kids the opportunity to experiment with new techniques. Each of the three main chapters-drawing from life, drawing from images, and inventive drawing-focuses on techniques to explore, such as observation, mark making, shadow, line, composition, detail, contour, and perspective. Drawing Workshop for Kids strives to inspire children to investigate drawing and develop their own approach to art, building creativity and confidence"--Provided by Publisher